Cook90 : the 30-day plan for faster, healthier, happier meals - Tamarkin, David (Little, Brown and Company, 2018)
Can you COOK90? It's easier than you think. For 30 days, challenge yourself to cook every meal--and you'll transform the way you eat and feel. The 150,000+ people who take the COOK90 challenge every year know that cooking for yourself is one of the most satisfying, effective, and easy ways to improve your wellbeing. With expert support from the editors of Epicurious, the web's most trusted recipe site, you'll say goodbye to pricey takeout, crummy pizza delivery, and fast food that's no good for you. And you'll say hello to all the benefits of home cooking: healthier and more delicious meals, a fatter wallet, a clearer mind, and sharper skills. With more than 100 recipes, strategies, and four weeks of meal plans for every way of eating, you can save time, money, and sanity with a simple promise: I will not rely on restaurants, roommates, Cups o'Noodles, or my family to feed myself. Instead, enjoy meals like: Baked Feta with Chickpeas and Greens, Steak Soba Salad, Braised Rotisserie Chicken with Bacon, Tomatoes, and Kale. Start your day with Perfect 7-Minute Eggs or Cocoa Oats with Yogurt, Honey, and Hazelnuts And end it with a Cinnamon-Chocolate Chunk Skillet Cookie or Salted Almond Apple Crisp. And you'll do it all without upending your life. By repurposing leftovers and planning ahead, you make cooking work for your schedule, not the other way around. Take the COOK90 challenge, and become a better, faster, healthier, happier cook.